Uji Viskositas Bahan Bakar Cair Hasil Proses Pirolisis Sampah Plastik Jenis HDPE, LDPE, dan PP - Kefi, Paulina Loveiana; Suarnadwipa, I Nengah; Adnyana, I Wayan Bandem (Teknik Desain Mekanika; Vol 13 No 3 (2024): Juli 2024 : Teknik Desain Mekanika, 2024)
Abstract This research is aims to find out the ability of plastic waste, in particular HDPE (High Density Polyethylene), LDPE (Low Density Polyethylene) and PP (Polypropylene), to be converted into liquid fuel through the pyrolysis process using the pyrolizer with designed specifications. The liquid fuel obtained is tested for its physical properties, which is viscosity. By knowing the viscosity of the liquid fuel from the pyrolysis process of plastic waste, it can later be compared with the viscosity of commercial fuel oil in Indonesia to find out the similarities. After performing the pyrolysis process on HDPE, LDPE and PP plastic waste using the specifications of the designed pyrolizer, all three can be converted into liquid fuel. With the specifications of the pyrolizer used in this research, it produces viscosity characteristics that are in the same range for the three liquid fuels (± 0,7 cP). The level of viscosity of the three liquid fuels compared to the viscosity of fuel in Indonesia is close to that of gasoline and kerosene. Keywords: Pyrolysis, Plastic Waste, Plastic Waste Handling, HDPE, LDPE, PP, Liquid Fuel, Pyrolysis Oil, Viscosity